MANAGING YIELD AND YIELD ATTRIBUTES OF TRITICALE IN A DEFICIT IRRIGATION SYSTEM WITH METHANOL FOLIAR APPLICATION - Mehdi KHOSHKHARAM; Mohamad Hesam SHAHRAJABIAN (Journal of Applied Life Sciences and Environment, 2021)
Triticale is mainly grown for feed grain and biomass production for thatching straw and general human use. A combined analysis with a factorial layout in the two years of 2016 and 2017 with five replications was used to evaluate the yield and yield components of triticale under different methanol concentrations and irrigation managements in Isfahan, Iran. Irrigation treatments consisted of irrigation on the basis of 70%, 80%, 90% and 100% crop water requirements, and methanol treatments as foliar application on the basis of 15% methanol concentration, 30% methanol concentration and control treatment (0%). Methanol application influence on one hundred grain weight was significant. The maximum plant height, number of tillers, Leaf area index (LAI), leaf area duration (LAD), one hundred grain weight, grain yield, biological yield, harvest index and protein content were achieved in irrigation on the basis of 100% crop water requirement. The maximum plant height, number of tillers, LAI, LAD, one hundred grain weight, grain yield, biological yield, harvest index and protein were obtained in 2017. Foliar methanol application with 15% concentration obtained the maximum plant height, LAI, LAD, one hundred grain weight, biological yield, soil plant analytical development (SPAD) and protein percentage. The results of this experiment suggest that methanol can aid in alleviating the effects of drought stress on triticale in the climatic condition of Isfahan. It is concluded that triticale cultivars performed better in 2017, with 15% concentration of methanol application and irrigation on the basis of 100% crop water requirement.